Sosialisasi Pembuatan Wedang Pokak Untuk Meningkatkan Imunitas di Tengah Pandemi COVID-19 di Kelurahan Peneleh Kota Surabaya - Heidy Arviani; Rohmatul Afrida Nor Laili; Septiana Dina Mahiro (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
The city of Surabaya is one of the cities in East Java with very high positive cases of COVID-19. Apart from adhering to health protocols, COVID-19 can be cured by itself or a self-limiting disease. Having a strong immune system is a way to fight viruses. Family Medicinal Plants (TOGA) are used to increase body immunity as a preventive measure to avoid contracting COVID-19. This community service activity was carried out in Peneleh Village, Genteng District, Surabaya City with one of its work programs being the socialization of making wedang pokak and distributing wedang pokak to the community. The outputs resulting from this activity include; (1) there is a video tutorial for making wedang pokak uploaded on the youtube channel "KKN 8 Peneleh Sby", the distribution of video tutorial links to the head of LKMK, secretary of the village head, and head of PKK RW 16; (2) Uploading posters about tools and materials, how to make wedang pokak, and the benefits of wedang pokak on several social media platforms, namely Instagram, Twitter, and Facebook; (3) distribution of 100 bottles of wedang pokak to the community of RW 16 and the staff of Peneleh Village. Based on the results of a survey of residents of Peneleh Village who have consumed wedang pokak, residents said the effect felt was that the body felt warmer and fresher. The hope from this socialization is that residents in Peneleh Village can understand the benefits and know how to make wedang pokak. In addition, after consuming wedang pokak, it is hoped that the community will be able to avoid contracting COVID-19 due to increased immunity.